How to live : the groundbreaking lifestyle guide to keep you healthy, fit and free of illness - Thomas, Robert (Robert J.) (London : Short Books, 2020)
Professor Robert Thomas, one of Britain's leading oncologists and an expert in integrating nutritional and lifestyle strategies into cancer treatment, gives us the facts about everything from diet and exercise to sleep and sunbathing. His book doesn't just offer advice, it outlines in detail the underlying chemical pathways of our lifestyle choices. As Thomas explains, while we must all accept the DNA we are dealt, through achievable changes to our daily routine we can significantly improve the expression of our genes - helping us beat the odds of cancer and chronic disease.
Includes bibliographical references and index.
Keywords: Diet therapy -- Popular works; Cancer -- Diet therapy -- Popular works; Health and Wellbeing